2017
DOI: 10.1104/pp.16.01973
|View full text |Cite
|
Sign up to set email alerts
|

Disrupting Flavone Synthase II Alters Lignin and Improves Biomass Digestibility

Abstract: Lignin, a ubiquitous phenylpropanoid polymer in vascular plant cell walls, is derived primarily from oxidative couplings of monolignols (p-hydroxycinnamyl alcohols). It was discovered recently that a wide range of grasses, including cereals, utilize a member of the flavonoids, tricin (39,59-dimethoxyflavone), as a natural comonomer with monolignols for cell wall lignification. Previously, we established that cytochrome P450 93G1 is a flavone synthase II (OsFNSII) indispensable for the biosynthesis of soluble t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
125
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(130 citation statements)
references
References 93 publications
4
125
1
Order By: Relevance
“…We also analyzed the distribution of cellulosic and hemicellulosic glycans using a two‐step acid‐catalyzed hydrolysis method (Chen et al ., ; Lam et al ., ). It was confirmed that, as is typical in other grasses, both OsC3 ′ H1 ‐KD and wild‐type cell walls were composed mainly of crystalline cellulose and amorphous arabinoxylans.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…We also analyzed the distribution of cellulosic and hemicellulosic glycans using a two‐step acid‐catalyzed hydrolysis method (Chen et al ., ; Lam et al ., ). It was confirmed that, as is typical in other grasses, both OsC3 ′ H1 ‐KD and wild‐type cell walls were composed mainly of crystalline cellulose and amorphous arabinoxylans.…”
Section: Resultsmentioning
confidence: 97%
“…Enhanced saccharification in lignin‐depleted cell walls has been well documented in the literature. With rice, our group has reported reduced biomass recalcitrance for CAD ‐ (Koshiba et al ., ), CAldOMT ‐ (Koshiba et al ., ) and FNSII ‐downregulated (Lam et al ., ) rice plants which all displayed decreased lignin content.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Consequently, as we previously proposed for Zm FNSI, it is possible that the regulation of both anthocyanin and flavone biosynthesis by the same regulators might be necessary to achieve an accurate balance of these compounds for pigmentation as well as to stabilize anthocyanins. On the other hand, it was recently demonstrated that tricin, a flavone that functions as a nucleation site for lignification in monocot species is not accumulated in fnsII rice mutants resulting in reduced lignin content (Lam et al, ; Lan et al, ). Thus, the possibility remains that either or both maize FNS enzymes can be involved in lignification, supplying apigenin to be further channeled to tricin biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…(). Regenerated plants and isolated OsCAld5H1 ‐KO mutant lines were grown to maturity in potting soil under growth chamber conditions as described previously (Lam et al ., ). OsCAld5H1 ‐KD and OsCAld5H1 ‐OX plants (T 3 generation) were generated and grown to maturity under greenhouse conditions as described previously (Takeda et al ., ).…”
Section: Methodsmentioning
confidence: 97%